Factors associated with general practitioners' contacts with sick-listed patients' employers: A Swedish nationwide questionnaire study. Issue 4 (June 2023) - Nordling, Paula; Alexanderson, Kristina; Hensing, Gunnel; Lytsy, Per
Background: General practitioners' (GP) contacts with sick-listed patients' employers have been shown to be of importance for return to work. This study aimed to explore GPs' contacts with sick-listed patients' employers and factors associated with such contacts. Methods: In this cross-sectional study, 4228 GPs responded to a nationwide questionnaire about sickness certification (SC) practices. Outcomes of interest were participation in stakeholder meetings, having other contacts with employers, and satisfaction with employer contacts. Logistic regression models were used to investigate associations with factors related to the GP and the GP's workplace. Results: Among GPs, 34.8% participated in stakeholder meetings and 15.1% had other employer contacts; 39.4% had any or both of these contacts. Of GPs who had contacts with patients' employers, 65.8% were satisfied with the contacts. GPs regularly collaborating with rehabilitation coordinators had the strongest adjusted odds ratio (OR) for participating in stakeholder meetings, OR 2.72 (95% confidence interval (CI) 2.24–3.31), and having other contacts with employers, OR 3.85 (95% CI 2.85–5.21). Other factors positively associated with employer contacts were being a specialist, collaborating with other health professionals, finding employer contacts valuable, and having a joint SC routine/policy at the clinic. GPs who did not find SC problematic, had managerial support, or had enough resources for SC tasks were more likely to be satisfied with their employer contacts. Conclusions: Both physician characteristics and organizational factors had importance for GPs' contacts with sick-listed patients' employers. The findings imply that GPs' collaboration with patients' employers may be improved by interventions targeting both individual and organizational factors.